A REHABILITATION PROGRAM PROPOSED FOR STRENGTH AND BALANCE EXERCISES AND ITS IMPACT ON SITTING AND STANDING SKILLS OF CHILDREN WITH FLACCID CEREBRAL PALSY - Asst. Prof. Ali Bdewi Taboor (PhD) (Proximus Journal Publishing, 2024)
A body of studies highlighted the role of exercise and training in helping children with Flaccid Cerebral Palsy to perform daily movements. These exercises strengthen the muscles responsible of movement and increase the muscle tone. Moreover, flexibility exercises restore the range of motion of joints and extend the restricted muscles, ligaments and tendons, supporting children in sitting and standing as well as other movements such as crawling and walking. As a therapist at the Cerebral Palsy Rehabilitation Center for Children, the researcher observed, as a research problem, children’s inability to sit and stand as a result of weakened muscle and imbalance in agonist and antagonist muscles, in addition to lack of flexibility as a result of ligaments and tendons shortness. Hence, the study aims to identify the relationship between strength and balance and their impact on the sitting and standing skill in children with cerebral palsy, and to identify the strength and balance development and their impact on the sitting and standing skills in children with cerebral palsy. The researcher uses the experimental method to tackle the research problem using a single group method. The research sample includes (12) children aging (2-4) years of the Specialized Rehabilitation Center of Patients with Cerebral Palsy and Walking Difficulty. All members of the sample suffer from the flaccid or soft type. The results indicate that the more child with adequate strength are more capable of performing the basic movement skills such as sitting and standing. In addition, children possessing balance, are more able to sit and stand stably, and that regular exercises based on scientific foundations lead to building muscle strength.
Keywords: Rehabilitation; Flaccid; Cerebral